Purpose-driven marketing strategies - Štefancová, Ema (2024)
The aim of the bachelor's thesis was to analyze and evaluate the marketing strategies of three purpose-driven brands, how do they communicate with the customer and also present their purpose. Further research has shown that not all of the brands actually do prefer marketing their purpose, and some do not focus on activating it; however, they still promote themselves with it. The purpose positioning without action leads to a current wave of woke-washing, which, as research has indicated, pushes customers even further away from the purpose due to authenticity concerns.